Prognostic significance of abnormal P wave morphology and PR-segment displacement after ST-elevation myocardial infarction. (15th October 2015) - Lu, Marvin Louis Roy; Nwakile, Chinualumogu; Bhalla, Vikas; De Venecia, Toni; Shah, Mahek; Figueredo, Vincent M.
Abstract: Introduction: Atrial infarction is uncommonly diagnosed and data on its significance are limited. Its incidence in ST-elevation myocardial infarction (STEMI) reportedly ranges from 0.7–42%. Certain atrial ECG changes, such as abnormal P wave morphology suggestive of atrial involvement have been associated with 90-day mortality after STEMI. However, whether atrial ECG changes are associated with short (30-day) or long-term (1-year) mortality have not been studied. Methods: We examined index ECG in 224 consecutive STEMI. Demographics, clinical variables, peak troponin I, ejection fraction, and angiographic data were collected. Atrial ECG patterns were examined and correlated with mortality. Results: Length of stay was longer with abnormal P waves ( p  = 0.008) or PR displacement in any lead ( p  = 0.003). Left main coronary disease was more prevalent with abnormal P wave ( p  = 0.045). Abnormal P wave morphology in any lead was associated with higher 30-day (OR 3.09 (1.35–7.05)) and 1-year mortality (OR 5.33 (2.74–10.36)). PR displacement in any lead was also associated with increased 30-day (OR 2.33 (1.03–5.28)) and 1-year mortality (OR 6.56 (3.34–12.86)). Abnormal P wave, PR depression in II, III and AVF, and elevation in AVR or AVL were associated with increased 1-year mortality (OR 12.49 (5.2–30.0)) as was PR depression in the precordial leads (OR 21.65 (6.82–68.66)). After adjusting for age, ejection fraction, peak troponin I, and left main disease, PR displacement in any lead was associated with increased 1-year mortality (adjusted OR 6.22 (2.33–18.64)). Conclusion: PR segment displacement in any lead, found in 31% of patients with STEMI, independently predicted 1-year mortality.